Geographical Determinants and Sacred Topography: Hadhrami Sayyid Migration to Panthalayini and Its Historical-Spatial Impact on Malabar's Islamic Landscape - Muhammed Fatheen Mk (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
This paper examines the historically significant yet understudied geographical dimensions of Hadhrami Sayyid and Sufi migration to Panthalayini near modern-day Quilandi, analyzing how physical geography shaped both settlement patterns and subsequent religious-cultural developments. Panthalayini's distinctive promontory hills and protective rock formations extending into the sea created an ideal natural harbor that positioned it among Malabar's premier ports. This geographical advantage established it as a crucial intermediary station for diverse pilgrimage routes, including those to Adam's Peak in Ceylon and for ships traversing from Iraq to China during the Abbasid era. Drawing upon Fernand Braudel's longue durée approach and Yi-Fu Tuan's concept of topophilia, this study explores how Panthalayini's sacred geography attracted and sustained over thirty Hadhrami Sayyid clans, including the Bafaqeeh, Haddad, Jifree, Saqaaf, and Aidroos families. The research elucidates how monsoon wind patterns—what Pliny the Elder in his Natural History identified as the Western Hippalos winds—functioned as natural mechanisms facilitating migration, with ships from Cape Diyagroos targeting Panthalayini as their destination. These environmental factors created what might be termed "monsoon bridges" that facilitated the continuous transfer of people, ideas, and practices between the Arabian Peninsula and Malabar Coast. The paper further investigates how geopolitical transformations, particularly the Portuguese intrusions into both Yemeni and Malabar ports, accelerated Hadhrami migration while reshaping settlement hierarchies along the coast. Through critical analysis of genealogical texts including Shamsuddaheera and Koukabudduriyya, supplemented by Badeeb's recent genealogical research and the well- preserved Aidroos Ratheeb documents, the study reconstructs migration patterns and their geographical determinants. Beyond migration mechanics, the research examines how Hadhrami settlers utilized local topography to establish spiritual centers that attracted disciples from across the Indian Ocean rim, creating nodes in an extended network reaching Gujarat, Aceh, and Bombay. Methodologically, this work combines qualitative approaches—including architectural analysis of local monuments, archival research, and interviews with clan members—with spatial analysis techniques to map the distribution of Hadhrami-influenced mosques and sacred sites. This interdisciplinary approach reveals how geographical features influenced not only initial settlement choices but also subsequent cultural production, exemplified by the Hadhrami supervision of hookah manufacturing that leveraged local craftsmanship traditions.The study ultimately contributes to historical geography by demonstrating how physical landscape features and maritime connections created conditions for Panthalayini's emergence as Kerala's foremost center of Hadhrami Sayyid presence, while illuminating broader patterns of religiously-motivated migration within the Indian Ocean world.